Supply Planning Optimization Under Uncertainties in Vaccine Manufacturer - Setiono Djojopoespito (Journal of World Science, 2025)
Indonesian and global health issues that influence each other's welfare and standard of living create the need for constant availability of vaccines that can be relied upon by the public and also the current competition in the vaccine industry that requires precise and efficient sales and operational planning to be able to meet customer needs in the market. This needs to be supported by a supply planning process, where all parties in supply line can coordinate in achieving demand fulfillment. However, in its implementation, there are several obstacles, including uncertainties in demand planning, facility and equipment downtime, regulation changes, distortion of information between lines of production, engineering division, material resource planning, due to different targets, poor communication, processing speed, accuracy and synchronization of data to the system. In this Journal, a supply planning optimization  framework concept will be proposed that makes the cross-functional alignment at a vaccine company in Indonesia more effective and efficient. In this journal, key aspects of supply planning will be discussed that can influence the direction of fulfillment planning in the company. A research approach through design thinking with related functions will be used to extract information in more depth. It is hoped that the resulting framework design can be a reference not only for practitioners but also for academics in understanding the importance of the role of supply planning which is able to integrate cross-functional interests in the supply chain.